Evaluasi Implementasi Proyek Sistem Aplikasi Terintegrasi Persediaan, Pembelian dan Penjualan: Studi Kasus Cyber Project di PT Pura Mayungan - Widjaya, Iwan Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2012)
In industry field, designing products that meet the criterias and expectations of the consumers is a must. PT Pura Mayungan as an industry panel company obtained a Cyber Project which required a particular project management system. In the meantime, the regulation and monitoring of all activities related to the cyber panel have not been well integrated as in the activities of inventory, purchasing, and sales towards the cyber project focusing. This causes difficulties in generating information needed by the management. Thus, a project management system was built to assist in the operation management activities including purchasing, inventory and sales. Besides, there was a need to build a computerized information system specifically for handling the calculation and recording of inventory and transactions to improve company performance. In this research two methods were implemented: analysis and data collection through literature evaluation. This research concluded that the lack of regulation and monitoring would bring a lot of difficulties in delivering information.